I-1 is the polynomials because I is the linear term and 1 is the constant
Answer-
<em>The inverse of
is </em>
![\boxed{\boxed{y=\log_3 x}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7By%3D%5Clog_3%20x%7D%7D)
<u>Solution-</u>
The given function is,
![y=3^x](https://tex.z-dn.net/?f=y%3D3%5Ex)
We can get the inverse by interchanging he variable x and y among themselves and then separating each variables.
So in the inverse would be,
![\Rightarrow x=3^y](https://tex.z-dn.net/?f=%5CRightarrow%20x%3D3%5Ey)
Taking log of both sides,
![\Rightarrow \log x=\log 3^y](https://tex.z-dn.net/?f=%5CRightarrow%20%5Clog%20x%3D%5Clog%203%5Ey)
As,
![\log a^b=b\times \log a](https://tex.z-dn.net/?f=%5Clog%20a%5Eb%3Db%5Ctimes%20%5Clog%20a)
Applying the same,
![\Rightarrow \log x=y\times \log 3](https://tex.z-dn.net/?f=%5CRightarrow%20%5Clog%20x%3Dy%5Ctimes%20%5Clog%203)
![\Rightarrow y=\dfrac{\log x}{\log 3}](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D%5Cdfrac%7B%5Clog%20x%7D%7B%5Clog%203%7D)
As,
![\log_b a=\dfrac{\log a}{\log b}](https://tex.z-dn.net/?f=%5Clog_b%20a%3D%5Cdfrac%7B%5Clog%20a%7D%7B%5Clog%20b%7D)
Applying the same,
![\Rightarrow y=\log_3 x](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D%5Clog_3%20x)
Therefore, the inverse of
is
.
U would subtract 2 an 3 from 56 using a variable x
56-2-3=x
X=51